Stability Analysis of Nickel Haul Road Embankment Slopes in Southeast Sulawesi - Granitio Irwan, Andesta; Mirza Rezky, Danu (Indonesian Geotechnical Journal, 2025)
The stability of embankment slopes is strongly influenced by the embankment material. Embankments are often constructed for mining haul roads, and those roads are subjected to large loads with high intensities. In this paper, stability analysis of a nickel haul road in Southeast Sulawesi is presented. For the case presented in this paper, the embankment is constructed on a saprolite layer using lateritic soil. Boreholes were conducted along the haul road to determine the soil profile. Disturbed samples of the lateritic soil were also taken to obtain its compaction behaviour and shear strength. Based on the soil stratigraphy and fill material properties, a parametric study varying the slope height (2.5 m to 10 m) and slope inclination (25º to 45º) is conducted. The results show that safety factors vary approximately linear with slope inclination, while safety factors reduce with increasing slope height, but at a reducing rate. Overall, even at the highest slope height and steepest slope inclination, a factor of safety higher than 1.3 is still obtained. That means the haul road embankment can be built safely for the site analyzed in this paper